A comparative study of magnetic seals by ferrofluids, magnetorheological fluids and magnetic powders - Li, Zhenghao; Li, Decai (Frontiers in Materials, 2022)
Magnetic seals as a class of non-contact sealing technology have been a research focus. In these seals, magnetic materials, usually ferrofluids or magnetorheological fluids are attracted in sealing gaps as sealing medium. Recently, a novel sealing method using nano-micron sized magnetic powders has been raised up as well. However, the working performance of these magnetic seals has not been studied thoroughly and comparatively yet. Here, we provide a comparative study of magnetic seals by ferrofluid, magnetorheological fluid and magnetic powder theoretically and experimentally. The formulas of pressure capability are derived based on their different properties. A modified empirical formula of magnetic powder seals is proposed, taking the frictional effect into consideration. The magnetic field distribution is calculated by the finite element method. Finally, a test bench for static magnetic seals is established. The pressure capability and leakage rate of three materials are measured by sealing experiments. The differences in mechanism of pressure transfer and the ability of self-recovery are discussed. This research summarizes the characteristics of different magnetic seals, and provides a guidance for sealing medium selection and structure design.